(untitled) (Journal of Analytical Oncology, 2018)
Introduction: The number of prostate cancer detected late because of the lack of means of investigation allowing a proximity screening, the poverty which characterize north are the two main elements which led us to lead this study which had for objective to shown the value of using rapid PSA screening tests. Method: We conducted a cross-sectional analytical study in the city of Ngaoundere and Garoua for a period of 5 months. Results: A total of 220 PSA level assays were performed over the 5-month period of our study with variations between the two selected centers. Of 30 samples used to study the sensitivity of rapid PSA screening tests, 22 were positive and 8 negative. The concordance rate for the positive values of the rapid test strip test versus the assay was 100%. The concordance of negative values was 87.5%. In addition, in a sample of 41 patients, PSA tests were performed in 30 patients, or 73.17%, and diagnosed prostate cancer in 69.23% of diagnosed cancer cases. Conclusion: Rapid PSA screening tests are good tools for diagnosing prostate cancer when combined with other tools such as digital rectal examination and ultrasound.